2019
DOI: 10.3390/s19081796
|View full text |Cite
|
Sign up to set email alerts
|

A Computer Vision-Based Roadside Occupation Surveillance System for Intelligent Transport in Smart Cities

Abstract: In digital and green city initiatives, smart mobility is a key aspect of developing smart cities and it is important for built-up areas worldwide. Double-parking and busy roadside activities such as frequent loading and unloading of trucks, have a negative impact on traffic situations, especially in cities with high transportation density. Hence, a real-time internet of things (IoT)-based system for surveillance of roadside loading and unloading bays is needed. In this paper, a fully integrated solution is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 24 publications
0
55
0
1
Order By: Relevance
“…Apart from vehicle classification or detection, CNN is also able to recognize the working or idle state of earthwork machines, like excavators or trucks [45], and CNN-TL can benefit earthmoving operations or related construction management [27,46]. Other non-CNN machine vision methods also have applications in related areas, like vehicle collision prediction or construction machine detection, [47][48][49][50]. It can be seen that current vision-based deep learning researches mainly focus on the vehicle classification or state identification of earthwork machinery, and CNN and CNN-TL are widely applied.…”
Section: Vison-based Deep Learning In Related Areasmentioning
confidence: 99%
“…Apart from vehicle classification or detection, CNN is also able to recognize the working or idle state of earthwork machines, like excavators or trucks [45], and CNN-TL can benefit earthmoving operations or related construction management [27,46]. Other non-CNN machine vision methods also have applications in related areas, like vehicle collision prediction or construction machine detection, [47][48][49][50]. It can be seen that current vision-based deep learning researches mainly focus on the vehicle classification or state identification of earthwork machinery, and CNN and CNN-TL are widely applied.…”
Section: Vison-based Deep Learning In Related Areasmentioning
confidence: 99%
“…Around the world, many cities have adopted information and communication technologies (ICT) to create intelligent platforms within a broader smart city context, and use data to support the safety, health, and welfare of the average urban resident [1,2]. However, despite the proliferation of technological advancements, road traffic accidents remain a leading cause of premature deaths, and rank among the most pressing transportation concerns around the world [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two ways to support road users' safety; (1) passive safety systems such as speed cameras and fences which prevent drivers and pedestrians from engaging in risky or illegal behaviors; and (2) active safety systems which analyze historical accident data and forecast future driving states, based on vehicle dynamics and specific traffic infrastructures. A variety of studies have reported on examples of active safety systems, which include (1) the analysis of urban road infrastructure deficiencies and their relation to pedestrian accidents [6]; and (2) using long-term accident statistics to model the high fatality or injury rates of pedestrians at unsignalized crosswalks [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer vision-based methods reduce costs and display real-time sequence images to observe multiple objects. Studies [17,18] have proposed image-based vehicle detection methods, image fragmentation into gray levels, and segment area distribution analysis to detect the presence of vehicles. However, traditional image processing has difficulties with processing complex backgrounds such as streets, bright or dark targets, and large areas with occlusion, as well as with separating targets and backgrounds.Several machine learning algorithms and object classification methods have been developed over many years.…”
mentioning
confidence: 99%